Persepsi Mahasiswa Tentang Efektivitas Pembimbingan Akademik - Jalal, Novita Maulidya; Abdullah, Edi; Nadjamuddin, Lukman (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
The purpose of this study was to determine how students’ perceptions of the effectiveness of academic guidance (PA). The research method used is a one shot case study. The data were collected using a survey related to perceptions, then analyzed quantitatively with the percentage technique. Subjects were 102 students who were willing to take part in the research. The results of the study were 40.2% of the subjects felt that they were effective. The process of academic guidance so far is that 93.1% are generally known to function when they consult during KRSan, and 20.6% of subjects who consult related to personal (non-academic) problems. Thus it can be concluded that Faculty X Makassar students perceive the role of mentoring PA tends towards academic guidance and has not been perceived as non-academic guidance.